A new TLM algorithm to solve the Pennes's equation for dosimetry applications - Makhlouf, Oualid; Cueille, Marylene; Dubard, Jean-Lou (2015 European Microwave Conference (EuMC), 2015)
The study of the interaction of the waves with the living requires taking into account the thermal aspect. To estimate the temperature in biological environments, the Pennes's equation must be solved. This paper presents a new numerical scheme based on the TLM method particularly suitable for the dosimetry in highly heterogeneous environments. The advantage of the method is its ability to perform simulation at a time step 14 times larger than those used with existing techniques, resulting in a strong reduction of the CPU time. The validity of the new algorithm proposed is demonstrated through comparisons with the FDTD method.